2020
DOI: 10.1186/s12985-019-1275-9
|View full text |Cite
|
Sign up to set email alerts
|

Early fulminant BK polyomavirus-associated nephropathy in two kidney transplant patients with low neutralizing antibody titers receiving allografts from the same donor

Abstract: Background: BK Polyomavirus (BKPyV) causes premature graft failure in 1 to 15% of kidney transplant (KT) recipients. High-level BKPyV-viruria and BKPyV-DNAemia precede polyomavirus-associated nephropathy (PyVAN), and guide clinical management decisions. In most cases, BKPyV appears to come from the donor kidney, but data from biopsy-proven PyVAN cases are lacking. Here, we report the early fulminant course of biopsy-proven PyVAN in two male KT recipients in their sixties, receiving kidneys from the same deceas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Taken together, our results add another layer to interpreting the increased risk of BKPyV-DNAemia and nephropathy in KT patients in donor–recipient pairs having BKPyV-serotype mismatch [ 5 ], which has been solely attributed to lacking the corresponding genotype-specific NAbs [ 18 , 21 ]. Conversely, high NAbs in the recipient against the donor genotype may be a marker for matching genotype-specific T-cells [ 26 ], adding to the partial protection and earlier clearance of plasma BKPyV loads in many [ 22 , 49 , 50 ], but not all cases [ 28 ]. Other observational studies can also be discussed in the new light of our findings, which report significant correlations of decreasing BKPyV-specific T-cells from pre-transplant to post-transplant with increased risk [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our results add another layer to interpreting the increased risk of BKPyV-DNAemia and nephropathy in KT patients in donor–recipient pairs having BKPyV-serotype mismatch [ 5 ], which has been solely attributed to lacking the corresponding genotype-specific NAbs [ 18 , 21 ]. Conversely, high NAbs in the recipient against the donor genotype may be a marker for matching genotype-specific T-cells [ 26 ], adding to the partial protection and earlier clearance of plasma BKPyV loads in many [ 22 , 49 , 50 ], but not all cases [ 28 ]. Other observational studies can also be discussed in the new light of our findings, which report significant correlations of decreasing BKPyV-specific T-cells from pre-transplant to post-transplant with increased risk [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some variability in the viral DNA-genome may arise by deamination of the antisense strand by the apolipoprotein B editing complex (APOBEC) 3, thereby introducing point mutations in the VP1 -gene encoding the major viral capsid protein Vp1 [ 25 ]. Although antibody titers to BKPyV virus-like particles generally correlate with BKPyV-specific CD4 T-cells [ 26 ], some reports indicate lack of correlation of plasma BKPyV loads with the emergence of BC-loop mutations or with rising NAb titers [ 27 , 28 ]. Although immune control at the level of the viral capsid, and specifically by BKPyV-Nabs, is likely to be important in protecting from systemic spread of the virus, recent data have demonstrated that plasma BKPyV loads in KT patients do not result from BKPyV virions [ 29 ], but mostly represent DNAse-sensitive, unprotected genome fragments similar to what has been reported for cytomegalovirus (CMV) [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…KTRs with low titers of genotype-specific neutralizing antibodies have also been identified as high risk for early fulminant donor-derived BKPyV-DNAemia and BKPyVAN. 35 In one study of 114 pediatric KTRs, BKPyV-specific CD4 T cells, ≥0.5 cells/µL and/or BKPyV-specific CD8 T cells ≥0. This study has the expected limitations of a single-center observational study, reflecting our specific population and clinical approach to management.…”
Section: Ta B L E 2 Basic Demographicsmentioning
confidence: 99%
“…However, this virus does not cause disease in immunocompetent individuals due to functional T-cell immunity. [1][2][3][4] In kidney transplant recipients (KTR), infection with BKV can be progressive, proceeding from viruria to viremia to nephropathy. 5,6 BK viremia is important, given the association with BK nephropathy (BKN), impaired graft function, and premature graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…4,16,17 In one study, identical BK virus strains were detected in two KTRs who had each received a kidney from the same deceased donor. 3 To date, most literature describing BK viremia in KTRs has focused on recipient characteristics to assess risk.…”
Section: Introductionmentioning
confidence: 99%